Comparative study of Q-Switched erbium doped fibre laser with SWCNT-PVA saturable absorber of different ratios. - Ooi, Wei Ling (Penerbit Akademia Baru, 2023)
This paper intends to compare the performance parameters of passive Q-switched erbium-doped fibre laser (EDFL) ring cavity configuration by employing SWCNT-PVA as a saturable absorber (SA). The single-wall carbon nanotube-polyvinyl alcohol (SWCNT-PVA) SA thin film fabricated by drop-casting technique is physically characterised to understand its surface morphology and thickness. The laser diode (LD) characterisation is attained to understand the attributes of LD before inserting the SWCNT-PVA into the ring cavity. The SWCNT-PVA SA of ratios 1:1, 3:2 and 2:3 is inserted into the cavity for analysis and comparison with each other. The pulses obtained from the Q-switched laser show that SWCNT-PVA SA of ratio 2:3 is the best SA as it possesses excellent power related parameters of the highest output power of 3.45 mW and highest pulse energy of 36.12 nJ with its moderate repetition rate of 96.25 kHz and pulse width 4.76 ms. The envisaged laser is presumed to have representational implications throughout fibre optic sensing, biosensors, range finding, and other fields for better possible prospects.